2018
DOI: 10.1177/1687814018806102
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of external gas-assisted mold-temperature control for thin-wall injection molding

Abstract: Simulation and experimental testing were conducted on an external gas-assisted mold-temperature control combined with a pulsed cooling system used for thin-wall injection molding to determine its effect on the heating rate and temperature distribution of a mold surface. For mold heating via external gas-assisted mold-temperature control, a hot gas was directly discharged on the cavity surface. Based on the heat convection between the hot gas and the cavity surface, the cavity temperature rose to the target val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…Therefore, with the design shown in Figure 1 , the water mold temperature controller is the same as in the traditional injection molding process. As compared with other mold heating methods such as external induction heating [ 23 ] or external gas-assisted mold temperature control [ 29 ], this has the advantage of using an In-GMTC.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, with the design shown in Figure 1 , the water mold temperature controller is the same as in the traditional injection molding process. As compared with other mold heating methods such as external induction heating [ 23 ] or external gas-assisted mold temperature control [ 29 ], this has the advantage of using an In-GMTC.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…These issues can be addressed by directly heating the cavity surface. There are several methods that can support a high heating rate and good predictability without heating the entire cavity volume, for example, induction heating [ 22 , 23 , 24 , 25 ], high-frequency proximity heating [ 26 , 27 ], and gas-assisted mold temperature control (GMTC) [ 28 , 29 , 30 , 31 , 32 ]. The induction heating method has a very fast heating rate, which is a great advantage.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of heating the entire mold cavity volume, in recent years, many researchers have suggested the use of the mold surface heating method for molding with high cavity temperatures, such as in induction heating [17][18][19][20], high-frequency proximity heating [21,22], and gas-assisted mold temperature control (GMTC) [23][24][25][26][27][28][29][30]. The first two methods support a fast heating rate with a fairly good prediction ability.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to address this issue, instead of heating the entire volume of the mold plate, recent research has suggested new heating methods in which only the cavity surface is heated. To achieve this, many methods for mold heating have been suggested, such as hot gas heating [ 30 , 31 , 32 , 33 ], induction heating [ 34 , 35 ], and infrared heating [ 36 , 37 , 38 ]. These methods could support high mold temperatures for improving the melt flow length by reducing the amount of frozen layer formed during melt flow.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite achieving the target of reducing both the heating time and thermal energy wastage, the heating time was not adequately minimized. In general, when raising the cavity surface temperature to that of the glass temperature of the plastic material, the required heating time is around 10 s or longer [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. This means that the molding cycle time is longer than the traditional cycle of around 10 s, i.e., it significantly exceeds 10 s.…”
Section: Introductionmentioning
confidence: 99%